2019
DOI: 10.1002/ajpa.23990
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling basal and accrued height‐for‐age for cross‐population comparisons

Abstract: Objectives: Current standards for comparing stunting across human populations assume a universal model of child growth. Such comparisons ignore population differences that are independent of deprivation and health outcomes. This article partitions variation in height-for-age that is specifically associated with deprivation and health outcomes to provide a basis for cross-population comparisons.Materials and Methods: Using a multilevel model with a sigmoid relationship of resources and growth, we partition vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…At the prenatal stage, both mechanisms benefit daughters without an older brother: there is no sibling rivalry and parents will invest in her while she is in utero anticipating that, with 50 percent chance, they are investing in their eldest son. 24 Post-birth, the negative effects of son-biased fertility-stopping behavior materialize as parents reoptimize fertility and expenditure decisions. Thus, at the postnatal stage, not having an older brother disadvantages girls through the fertility continuation mechanism.…”
Section: Implications Of Son-biased Fertility-stopping Behaviormentioning
confidence: 99%
“…At the prenatal stage, both mechanisms benefit daughters without an older brother: there is no sibling rivalry and parents will invest in her while she is in utero anticipating that, with 50 percent chance, they are investing in their eldest son. 24 Post-birth, the negative effects of son-biased fertility-stopping behavior materialize as parents reoptimize fertility and expenditure decisions. Thus, at the postnatal stage, not having an older brother disadvantages girls through the fertility continuation mechanism.…”
Section: Implications Of Son-biased Fertility-stopping Behaviormentioning
confidence: 99%
“…We focused on women aged 40–49 as they normally show maximal associations between BMI and wealth (Hruschka, Hackman, and Stulp 2019; Hruschka, Hadley, and Brewis 2014; Hruschka and Hadley 2016). For child growth outcomes, we focused on 12–59‐month‐old children as prior research has shown HAZ may not be a particularly reliable measure of nutrition among 0–11 month olds (Hackman and Hruschka 2020; Wright 2000). Adult BMI was calculated as weight (kg)/height (m) 2 , and we excluded cases with values below 10 or above 80.…”
Section: Methodsmentioning
confidence: 99%
“…Child A enjoyed adequate nutrition and low disease burden and reached her maximum potential height. By contrast, Child B had a genetic potential to grow much taller than child A in an optimal environment, but was chronically undernourished and subjected to substantial disease burden (Hackman & Hruschka, 2020). A one‐size‐fits‐all cutoff for height would make these two children look equally healthy, despite drastic differences in their environments and mortality risks.…”
Section: Origins Of One‐size‐fits‐all Approachesmentioning
confidence: 99%
“…Haiti's infant mortality rate is 50% greater and its GDP per capita is less than a third of India's. Yet, by the WHO growth standards, Haitian children seem to be doing much better than Indian children, with only 6% of Haiti's children classified as severely stunted compared to 14% in India (Hackman & Hruschka, 2020).…”
Section: There Is No Universal Trajectory Of Healthy Growth In Heightmentioning
confidence: 99%
See 1 more Smart Citation